(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Dyslipidemia and abnormal calcium homeostasis are metabolic complications of type 2 diabetes mellitus (T2DM), a metabolic illness that raises the risk of cardiovascular disease (CVD). The purpose of this research is to examine the connection between lipid profile characteristics and blood calcium levels in individuals with type 2 diabetes. Blood samples from 200 type 2 diabetic patients were analyzed for calcium, total cholesterol, triglycerides, low-density lipoprotein, and high-density lipoprotein levels in a cross-sectional research. Calcium levels were shown to be significantly inversely associated with LDL-C and TG levels, indicating that lipid problems in type 2 diabetic patients may be influenced by altered calcium metabolism.